2006
DOI: 10.1136/sti.2005.016014
|View full text |Cite
|
Sign up to set email alerts
|

Declines in HIV prevalence can be associated with changing sexual behaviour in Uganda, urban Kenya, Zimbabwe, and urban Haiti

Abstract: Changes in patterns of HIV prevalence in urban Kenya, Zimbabwe, and urban Haiti are quite recent and caution is required because of doubts over the accuracy and representativeness of these estimates. Nonetheless, the observed changes are consistent with behaviour change and not the natural course of the HIV epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
124
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(132 citation statements)
references
References 29 publications
(27 reference statements)
7
124
0
1
Order By: Relevance
“…1,9,10 Although there is new evidence of an increase in HIV infections in some parts of Uganda, 12 several other studies in both urban and rural areas have shown a tremendous decline in HIV prevalence associated with increased awareness and significant decrease in sexual behavior at risk. [12][13][14][15][16][17][18][19][20][21][22] The Uganda National sero and behavioural survey 2004/5 10 showed adult HIV prevalence declined from 18-30 % in the early 1990s to 6.4% in 2005. The report further showed an estimated 1.1 million Ugandans living with the HIV/AIDS in 2005 with lowest prevalence in the West Nile region (2.3%) and highest prevalence in Central region (8.5%), followed by North ern region (8.2%), Western region (6.9%) and Eastern region (5.3%).…”
Section: Introductionmentioning
confidence: 99%
“…1,9,10 Although there is new evidence of an increase in HIV infections in some parts of Uganda, 12 several other studies in both urban and rural areas have shown a tremendous decline in HIV prevalence associated with increased awareness and significant decrease in sexual behavior at risk. [12][13][14][15][16][17][18][19][20][21][22] The Uganda National sero and behavioural survey 2004/5 10 showed adult HIV prevalence declined from 18-30 % in the early 1990s to 6.4% in 2005. The report further showed an estimated 1.1 million Ugandans living with the HIV/AIDS in 2005 with lowest prevalence in the West Nile region (2.3%) and highest prevalence in Central region (8.5%), followed by North ern region (8.2%), Western region (6.9%) and Eastern region (5.3%).…”
Section: Introductionmentioning
confidence: 99%
“…The current study shows that age at first sexual intercourse was 15.4 years for Jamaicans, indicating a need to make contraceptives more freely available to adolescents. Young people in Jamaica are not atypical in engaging in unprotected and premarital sexual relationships, given that this phenomenon is also found in Thailand, 40,41 Indonesia, 16 the wider Caribbean, [7][8][9]15,42 Uganda, Kenya, Zimbabwe, and other African nations, [12][13][14]43,44 as well as some Latin American countries. 45 According to Crawford et al, 46 80% of pregnancies among adolescents were unwanted, and 40% of women in Jamaica were pregnant before the age of 20 years.…”
Section: Dovepressmentioning
confidence: 99%
“…In Jamaica, contraceptive prevalence has increased from 38% in 1975-76 to 64% in 1997, and 69% in 2007. 2,12 In spite of wide access to contraceptive methods such as the condom, developing countries, in particular Africa and the Caribbean, have seen widespread increases in human immunodeficiency virus (HIV), acquired immunodeficiency syndrome (AIDS), and/or other sexually transmitted infections (STIs), as well as in adolescent pregnancy, [12][13][14][15] all of which highlight infrequency of condom usage in these societies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reasons of what happened in Zimbabwe justify this anomalous delay! Actually prior to Mexico City conference, two major publications about the decline of HIV in Zimbabwe went practically unnoticed [3,4], despite the AIDS ambassador Mark Dybul's remarks on these unexpected trends: ''Perhaps one of the most interesting things is that the greatest behavior change was in abstinence and fidelity. The relative change in condom use was as not as remarkable'' [5].…”
mentioning
confidence: 99%